2009
DOI: 10.1007/s00330-009-1676-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left ventricular function assessment using phonocardiogram- and electrocardiogram-triggered 2D SSFP CINE MR imaging at 1.5 T and 3.0 T

Abstract: ACT's intrinsic insensitivity to interference from electromagnetic fields renders it suitable for clinical CMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…The study demonstrated that the true triggered images were superior to the self-gated images. There are some other approaches, too; recent studies applied an acoustic cardiac triggering mechanism using an MR-stethoscope that picks up the acoustic signals generated by the heart (12,13). This device was fully compatible with the ECG trigger unit of the MRI devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that the true triggered images were superior to the self-gated images. There are some other approaches, too; recent studies applied an acoustic cardiac triggering mechanism using an MR-stethoscope that picks up the acoustic signals generated by the heart (12,13). This device was fully compatible with the ECG trigger unit of the MRI devices.…”
mentioning
confidence: 99%
“…This device was fully compatible with the ECG trigger unit of the MRI devices. These studies indicated that the acoustically triggered images were equally good, if not superior, to the triggered images by ECG (13). A more precise and technically advanced device is still required to improve the cardiac triggering, even for, e.g., fetal cardiac MRI.…”
mentioning
confidence: 99%
“…The MHD effect creates electric potential related to blood flow, which is superimposed onto the ECG potential. This susceptibility to electromagnetic field (EMF) interference manifests itself in ECG waveform distortions already present in ECG traces acquired at 1.5 T and lower fields (2,5). As high and ultrahigh field MR becomes more widespread, the susceptibility of ECG recordings to MHD effects is further pronounced (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Contrary to the notion (5,8,18,19) that considers MHD effects as adverse concomitants of traditional ECG acquired in a magnetic field environment, this feasibility study explores the merits of MHD effects for cardiac-gated MRI. We propose that the MHD effect being inherently sensitive to magnetic flux density, flow orientation with respect to the magnetic field lines, and velocity of an electrical charge carrier such as blood can be put to use as an alternative approach for registration of cardiac activity and for cardiac gating/triggering.…”
mentioning
confidence: 99%
“…Magneto hydrodynamic (MHD) effects severely disturb the electrocardiogram (ECG) [61][62][63] commonly applied for cardiac triggering and gating at clinical field strengths [64][65][66] (Figure 4). Distortions of the ECG's S-T segment are caused by the increased MHD impact during systolic aortic flow [67]. The S-T elevation might be mis-interpreted as an R-wave.…”
Section: Ancillary Devices For Cardiac Synchronizationmentioning
confidence: 99%